Organ-Specific Mechanisms of Transendothelial Neutrophil Migration in the Lung, Liver, Kidney, and Aorta - Maas, Sanne L.; Soehnlein, Oliver; Viola, Joana R. (Frontiers in Immunology, 2018)
Immune responses are dependent on the recruitment of leukocytes to the site of inflammation. The classical leukocyte recruitment cascade, consisting of capture, rolling, arrest, adhesion, crawling and transendothelial migration, is thoroughly studied but mostly in model systems, such as the cremasteric microcirculation. This cascade paradigm, which is widely accepted, might be applicable to many tissues, however recruitment mechanisms might substantially vary in different organs. Over the last decade, several studies shed light on organ-specific mechanisms of leukocyte recruitment. An improved awareness of this matter opens new therapeutic windows and allows targeting inflammation in a tissue-specific manner. The aim of this review is to summarize the current understanding of the leukocyte recruitment in general and how this varies in different organs. In particular we focus on neutrophils, as these are the first circulating leukocytes to reach the site of inflammation. Specifically, the recruitment mechanism in large arteries, as well as vessels in the lungs, liver and kidney will be addressed.